An Unusual Case of Myonecrosis - P. Mukhopadhyay; R. Barai; C. A. Philips; J. Ghosh; S. Saha (Case Reports in Endocrinology)
Diabetic Myonecrosis is a rare complication of long-standing Diabetes Mellitus Type 1 and 2. The most likely affected areas are of proximal lower limbs, mostly the quadriceps muscle. The presenting features are myriad and a diagnostic conundrum for the physician. There has been previously mentioned, through few case reports, the classical presentation of diabetes-related muscle infarction. Here we present a patient of diabetic myonecrosis, in whom the initial presentation of diabetes mellitus was that of bilateral symmetric proximal upper limb predominant muscle infarction, which has never been reported before.